Performance Quality Preference Heterogeneity in Major League Baseball. (April 2023) - Mills, Brian M.; Fort, Rodney
With few exceptions, the sports attendance demand literature assumes the intensity of fan responses to home and visiting team quality are homogeneous across the markets in a league. However, the theory of sports leagues makes no such assumption. In this paper, we empirically investigate heterogeneity in fan win preference intensity using Major League Baseball attendance. Using a generalized linear mixed model, we find evidence of substantial fan preference heterogeneity, toward both home and visiting team quality, across Major League Baseball markets. In addition to the demonstrated importance for empirical analysis, we detail how this also matters for league policy design.